Proposed changes ICER 2023 value assessment framework - I. R. Svechkareva; A. A. Kurylev (Реальная клиническая практика: данные и доказательства)
Since 2006, the Institute for Clinical and Economic Review (ICER) in the United States has assessed the clinical and economic value of innovative medical technologies and made pricing recommendations with the goal of achieving “sustainable access to highly effective treatments for all patients”. The methodological framework developed by ICER assesses the longterm economic value of health interventions and their availability in the shortest possible time.